PENDAMPINGAN PENGADAAN JARINGAN DAN PERANGKAT INTERNET DI DESA WISATA SANGKANJOYO KABUPATEN PEKALONGAN - Rahayu, Sri; Anggraeni, Desy; Jati, Rocky Prasetyo (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
Sangkanjoyo Village has carried out a diversification program for economic business for non-agricultural businesses, such as the development of the Sangkanjoyo Tourism Village. Efforts to expand the agricultural sector and diversify the economy towards the tourism industry are in dire need of supporting infrastructure, including information and communication technology. Internet is one of the most popular technologies in Sangkanjoyo Village. However, unstable internet connectivity is still a significant obstacle for Sangkanjoyo village. Therefore, it is necessary to procure and optimize the procurement of internet networks. The purpose of this community service program is assistance to the Sangkanjoyo village community, which is focused on optimizing internet network activities, namely the provision of internet networks and devices. This community service program increased community activity in supporting the tourism village growth program through internet technology.